„Гойда, Орки” на «священной войне»: предыстория трех символов российско‑украинской войны в русской словесности - Matveev, Evgenii (Slavia Orientalis, 2026)
The paper focuses on the literary origins of modern Russian propaganda and anti‑propaganda discourses. This article reconstructs the linguistic and cultural history of three expressions which were used in the debate between Ivan Okhlobystin and Maksim Pokrovskii in 2022 – holy war, goida and orcs. These expressions have become symbols of the ongoing Russo‑Ukrainian war. The research material comprises texts in Russian belonging to various genres, including works of Russian fiction. With the help of the collocation holy war, which used to serve and yet still serves as an analogy, the largest military conflicts in which Russia participated were described. The interjection goida, starting from Karamzin, was used in historical, historical‑fictional and pseudo‑historical texts as an exclamation of Ivan the Terrible’s oprichniks. The word orcs came to Russian literature from Tolkien’s fantasy works but this image was reinterpreted in connection with the ideas of counterculture. The history of the words goida and orcs in contemporary Russian literature and journalism demonstrates that they have changed their negative connotation into neutral or positive within modern military propaganda discourse. The actual literary prehistory identified for each of the lexical units examined allows one to pose the problem of the connection between Russian literature of the early 21st century and the Russo‑Ukrainian war.